Developing and supporting athlete wellbeing : person first, athlete second - Campbell, Natalie (Social psychologist); Brady, Abbe; Tincknell-Smith, Alison (New York : Routledge, 2022)
"This pioneering book in elite athlete wellbeing brings together the narratives of athletes and wellbeing practitioners in high performance sport with cutting edge theorising from world leading academics to explore pertinent mental wellbeing matters that present for elite athletes both during and after their careers. The journey of the elite athlete is considered from entering the high performance system as a youth performer through to retirement, with contributions illuminating the ways in which mental wellbeing can be impacted - both negatively and positively - through common place experiences. Methods of creating holistic high performance sports cultures, along with common mental wellbeing influencers such as parents, education, faith, injury, and (de)selection are explored, as well as the ramifications of uncommon events on mental wellbeing such as whistleblowing, legal disputes, psychological disorders, and COVID19. Drawing on this analysis the book then proffers thought provoking strategies for how the mental wellbeing of both athletes and staff can be understood, developed and supported, ultimately driving elite sport cultural transformation to put the person first and the athlete second. Each chapter presents the wellbeing experience from the vantage of the athlete or the wellbeing practitioner, followed by an academic unpacking of the situation. This makes the book a must read for students and researchers working in sport coaching, sport psychology, applied sport science or sport management, as well as practitioners interested in facilitating a duty of care for high performing athletes, and working in coaching, sport science support, athlete development programs, NGB policy and administration, or welfare services"--
Introducing Wellbeing Within the Holistic Athlete Development Journey -- The Holistic Wellbeing of Elite Youth Performers: U MATTER -- The Role of Parents and Family in the Wellbeing of Athletes -- Dual Careers and Athlete Wellbeing -- The Role of Coach Leadership in Promoting Athlete Wellbeing and Performance -- Supporting Athletes from Different Cultures and Nationalities: The Case of Women's Football -- The Impact of Selection and Deselection on Athlete Wellbeing: Australian Women's Cycling -- Supporting the Wellbeing for Athletes of Faith -- The Ableism of Athlete Wellbeing Support: Additional Needs of the Paralympic Athlete -- The Implementation of an Integrated Psychological Support Programme for Injured Athletes: "Stopping Athletes from Falling Off the Edge of the Cliff" -- Developing Caring Cultures in Football: A Model for Practice and Change -- Supporting an Athlete through Legal Action -- Wellbeing and Whistleblowing: What Happens? -- Supporting Athlete Careers and Retirement from the Vantage Point of Smaller National Governing Bodies -- Athlete Welfare, Stakeholder Responsibility, and Ethics of Care in Elite Sport: An Examination of Para-sport Organisation Approaches in France -- Fighting a System Built to Exclude Queer(ing) Bodies: An Imperative for Athlete Wellbeing -- The Role of Athletic Identity Foreclosure in the Development of Poor Athlete Mental Health -- Supporting Athlete Wellbeing During a Global Pandemic: The Case of COVID19 -- Postscript.
Description based upon print version of record.
Keywords: Sports -- Psychological aspects; Exercise -- Psychological aspects; Athletes -- Mental health; Coach-athlete relationships -- Moral and ethical aspects; Well-being.; SPORTS & RECREATION / General; SPORTS & RECREATION / Sports Psychology; SPORTS & RECREATION / Coaching / General